Chiral Pharmacokinetics and Metabolite Profile of Prolonged-release Ketamine Tablets in Healthy Human Subjects. (August 2021) - Hasan, Mahmoud; Modess, Christiane; Roustom, Tarek; Dokter, Anne; Grube, Markus; Link, Andreas; Rey, Hélène; Adler, Stefanie; Meissner, Konrad; Siegmund, Werner
Abstract : Background: The anesthetic ketamine after intravenous dosing is nearly completely metabolized to R- and S-stereoisomers of the active norketamine (analgesic, psychoactive) and 2, 6-hydroxynorketamine (potential analgesic, antidepressant) as well as the inactive dehydronorketamine. Oral administration favors the formation of 2, 6-hydroxynorketamines via extensive presystemic metabolism. The authors hypothesized that plasma exposure to 2, 6-hydroxynorketamines relative to the psychoactive ketamine is greater after prolonged-release ketamine tablets than it is after intravenous ketamine. Methods: Pharmacokinetics of ketamine after intravenous infusion (5.0 mg) and single-dose administrations of 10, 20, 40, and 80 mg prolonged-released tablets were evaluated in 15 healthy white human subjects by means of a controlled, ascending-dose study. The stereoisomers of ketamine and metabolites were quantified in serum and urine by validated tandem mass-spectrometric assays and evaluated by noncompartmental pharmacokinetic analysis. Results: After 40 mg prolonged-release tablets, the mean ± SD area under the concentrations–time curve ratios for 2, 6-hydroxynorketamine/ketamine were 18 ± 11 (S-stereoisomers) and 30 ± 16 (R-stereoisomers) compared to 1.7 ± 0.8 and 3.1 ± 1.4 and after intravenous infusion (both P < 0.001). After 10 and 20 mg tablets, the R-ratios were even greater. The distribution volumes at steady state of S- and R-ketamine were 6.6 ± 2.2 and 5.6 ± 2.1 l/kg, terminal half-lives 5.2 ± 3.4 and 6.1 ± 3.1 h, and metabolic clearances 1, 620 ± 380 and 1, 530 ± 380 ml/min, respectively. Bioavailability of the 40 mg tablets was 15 ± 8 (S-isomer) and 19 ± 10% (R-isomer) and terminal half-life 11 ± 4 and 10 ± 4 h. About 7% of the dose was renally excreted as S-stereoisomers and 17% as R-stereoisomers. Conclusions: Prolonged-release ketamine tablets generate a high systemic exposure to 2, 6-hydroxynorketamines and might therefore be an efficient and safer pharmaceutical dosage form for treatment of patients with chronic neuropathic pain compared to intravenous infusion. Abstract : The hypothesis that systemic exposure to the 2, 6-hydroxynorketamines can be increased by administration of a prolonged release ketamine dosage form was tested in a controlled, five-period, ascending-dose pharmacokinetic study in 15 healthy volunteers. The (mean ± SD) oral bioavailabilities of S- and R-ketamine were 15 ± 8% and 19 ± 10%, respectively. The systemic exposure to the hydroxynorketamine stereoisomers after oral administration of 40 mg of prolonged-release ketamine was 10 to 11 times that after administration of a comparable intravenous dose (5 mg).